Effect of Some Chloride Salts on Swelling Properties of Expansive Soil (University of Khartoum Engineering Journal, 2022)
This paper aims to provide a proposed correlation for Sudanese crude oil in order to estimate solution gas oil- ratio directly without depending on laboratory measurements.There are many correlations that were utilized for a number of international crude oils. However, because the components of crude differ from region to region, it is difficult to use any specified correlation for different regions and that is simply because each region has its own properties. The core hypothesis of this paper is to find that there is a correlation between the solution gas- oil ratios as a function of the physical properties of the critical temperature, critical pressure, normal boiling temperature, bubble point pressure and gas specific gravity. In these the logarithmic regression method on Microsoft Excel Statistics Package programme used to find this correlation. The obtained results should that there are coefficients for correlation pilot. The correlations were tested using laboratory data in order to justify their accuracy and usefulness using statistical tools and graphics. The results obtained well agreed with laboratory results .The results were compared with other values obtained from international correlations which are used to calculate the solution gas oil ratio.The study indicates that this new correlation can predict well the solution gas oil ratio for Sudanese crude oil when compared to any other known correlations.